Dynamic Model Analysis for Unsteady Operating of Double V-Belt Drive System - Ameer A. K., Nabhan A., Mohamed R. El-Sharkawy,Rashed A. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Alignment issues of the transmission V-belt drive system using numerical model are one of the challenges we are trying to find ways to deal with them.Experiments and dynamic model analysis were performed to monitor and perdict of alignment issues of the transmission system.Various types of transmission system misalignment were investegated using the developed model. Using different two statistical parameters, RMS and Crest factor, the vibration level was monitored.The results obtained during the study confirmed that you have a type each type of alignment issues has an optimal way to deal with it in terms of locating the appropriate position to install the sensor.Moreover, the results displaythat it can used theRMS and CFstatistical parametersof the accelerationresponsesto detect and monitor of the transmission system misalignment.Furthermore, the mathematical model may be considered as an alternative method to detect vibration signals of the transmission system using the spring-mass system.